Precision in Memory Through Distinctive Processing. (February 2013) - Hunt, R. Reed
Any item that violates its current context will be well remembered, a phenomenon typically attributed to distinctiveness. Distinctiveness often is used as a synonym for difference, but, in fact, the beneficial effects of distinctiveness on memory arise only when both similarity and difference are encoded. In this article, I describe an approach modeled on a theory of similarity judgment that defines distinctive processing as the processing of difference in the context of similarity. Such processing has been shown to be highly diagnostic of particular events and of items within those events. Research predicated on this definition has shown impressive memory for target items, in addition to explaining how distinctive processing protects against incorrect memory. A focus on distinctive processing is a promising approach to understanding the precision that characterizes the normal operation of memory.